Pergaulan Bebas dalam Film Dua Garis Biru: Analisis Nilai-Nilai Tauhid dalam Perspektif Al-Qur'an - Fitriani, Siti Nuranisa; Jannah, Lestari Amalia; Yanti Akbar, Maulidina April; Arizki, Muhammad Fahmi; Firdaus, Dadan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the portrayal of free association in the film Dua Garis Biru (2019) and to analyze it through the lens of tawhid values in the Qur'an. Using a descriptive qualitative approach with content analysis and thematic tafsir (maudhu'i) methods, data were collected through observation of film scenes and dialogues, then linked to relevant Qur'anic verses and the interpretations of Tafsir Ibn Kathir and Tafsir Al-Mishbah. Findings indicate that the free association depicted in the film, from unbounded physical closeness to premarital pregnancy and family conflict, reflects a neglect of ghadhul bashar (guarding the gaze) and muraqabatullah (awareness of divine supervision) as affirmed in QS. Al-Isra (17): 32 and QS. An-Nur (24): 30-31. This research contributes to contemporary Qur'anic scholarship on popular cultural media and supports moral-religious literacy among Muslim youth.